A study: Artificial Neural Networks and its Applications - Jigyasu, Divayani (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 4 No 1 (2020): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
This paper mainly focuses on the Artificial Neural Networks and its associated application areas. In this paper, prediction and detection of human lung cancer using the concepts of Neural Networks has been discussed. Cancer (Lung cancer) is the leading cause of death in India and other countries as well. The early detection on this dangerous is very important. The prediction and the detection of lung cancer at early stages are being determined by using the concepts of image processing with suitable artificial neural networks models. Artificial Neural Networks has a significant role in the field of medicine. Nowadays, most of diseases are being cured with the help of artificial intelligence and the world is witnessing a revolutionizing era. How to cite this article: Jigyasu D, Ganaie RA. A Study: Artificial Neural Networks and its Applications. J Adv Res Appl Arti Intel Neural Netw 2020; 4(1): 7-9.